SOME CONSIDERATIONS ABOUT THE CONCEPTS OF ECOLOGICAL COMPETENCE AND ECOAESTHETIC COMPETENCE (Academia Science Repository, 2023)
In this article, the concepts of ecological and eco-aesthetic competence are scientifically analyzed, their explanations in various scientific literature are detailed, and detailed information is provided based on several sources. The reasons why the competency-based approach is becoming a priority in education today are given and explained. It is a characteristic aspect of the article to justify that a warm attitude towards nature and love for beauty serve as the basis of the above two concepts.